Assessment of health related quality of life using specific strabismus questionnaire on pre-and post-strabismus surgery in children with infantile esotropia and their parents - Ean, Tan Chew (2019)
Introduction: Children with infantile esotropia and their parents experienced various functional and psychosocial problems. However, there is insufficient knowledge regarding the impact of infantile esotropia as well as the effect of surgical correction towards the children and their parents. Objective: To evaluate HRQoL assessment on pre- and post-strabismus surgery in children with infantile esotropia and their parent/guardian by using Malay translated IXTQ. Methodology: This prospective study was conducted in Ophthalmology Clinics, Sabah Women and Children Hospital and Hospital Universiti Sains Malaysia from June 2017 until November 2018. The children and their parent/guardian were asked to answer Malay translated IXTQ at enrolment and three months after surgery. The total mean scores and three subscale scores which were functional, psychosocial and surgery, were calculated and compared before and after surgery. Result: A total of 34 children with infantile esotropia aged 8-17 years accompanied by one of their parent/guardian were recruited. Thirteen (38.2%) children had esotropia more than 50 prism dioptres. Thirty three (97.1%) children achieved successful alignment correction. Strabismus surgery had significantly improved the total mean scores in children after surgery, which was 62.87 preoperatively and 87.13 postoperatively (p < 0.001). There was statistically improvement in total mean scores in parent group, which was 37.07 preoperatively and 75.39 postoperatively (p < 0.001). Its three subscales also had significant increment of the score postoperatively (p < 0.001). Conclusion: The mean scores of HRQoL assessment in children with infantile esotropia and their parents were improved significantly after strabismus surgery.